Experimental study on propagation and attenuation regularity of landslide surge - Zu, Fuxing; Wang, Pingyi; Xu, Jiqing; Xie, Liquan (Penerbit Universiti Kebangsaan Malaysia, 2017)
On the basis of landslide surge model test by adopting generalized simulation of waterways, this paper, for the first time, established a four-dimensional mathematical model between wave height transmissibility rate and the initial wave height, water depth, azimuth angle as well as propagation distance through utilizing the method of tensor space mapping. Using the new model, we proposed an empirical wave field covering all areas of the channel including the attenuation area within the width of a landslide mass, the straight channel attenuation area outside the width of the landslide mass, the curved channel attenuation area and the after-curve attenuation area, which comprehensively reflects the progressive changes of surge wave factors. The transmissibility of wave height and propagation distance are in a bivariate negative exponential distribution, and the wave height gradually reduces and the attenuation also slows down as the propagation distance increases; wave height transmissibility rate, azimuth and propagation distance are in a trivariate negative exponential distribution, the attenuation of the wave height in the straight channel within the width of the landslide mass was the slowest, followed by that of wave in the straight channel outside the width of the landslide mass, and the attenuation of the wave height in the curved channel is the greatest. This empirical wave field was based on test data, scientifically abstracted the general regularity of the propagation and attenuation of landslide surge, which can be applied to similar analyses and forecasts on landslide surge and can scientifically and accurately determine the damage range of landslide surge.